The role of ONSD in the assessment of headache associated with Chiari malformation type 1 - Karadag, Mehmet Kürşat; Akyuz, Mehmet Emin; Sahin, Mehmet Hakan (Frontiers in Neurology, 2023)
Background Cough associated headache is the most common symptom in Chiari malformation type 1 (CM1). However, its pathophysiology and treatment are not clear. The aim of this study was to investigate the relationship between optic nerve sheath diameter (ONSD), an indicator of intracranial pressure, and headache and to investigate its predictive value on postoperative outcome. Methods In symptomatic CM1 patients, craniovertebral junction morphometric measurements and ONSD measurements were made from preoperative MR images, and headache intensities and characteristics were evaluated. After different surgical procedures, the clinical characteristics of the patients were evaluated according to the Chicago Chiari Outcome Scale, the change in headache intensity was assessed and the relationship with ONSD was evaluated. Results Preoperative headache intensity was significantly correlated with ONSD measurement (p < 0.01). Modified clivoaxial angle and ONSD were independent predictors of postoperative clinical outcome (p < 0.01). The procedure that achieved the greatest surgical enlargement of the foramen Magnum stenosis provided the best clinical outcome. Postoperative reduction in headache intensity and ONS diameter were correlated (p < 0.01). Conclusion The fact that ONSD is found to be wide in the preoperative period in CM1 patients indicates that the intracranial pressure is permanently high. This diameter increase is correlated with headache and is a valuable guide in the selection of the appropriate treatment method.